Mesoscale simulation of a very heavy rainfall event over mumbai, using the weather research and forecasting (wrf) model - Kirtsaeng S. (2014)
The simulation of a severe weather phenomenon, in this case the unprecedented heavy rainfall over Mumbai in India on July 26, 2005, was selected for this study. The mesoscale numerical weather prediction model used here utilized the Advanced Research Weather Research Forecast model (version 3.0.1), as developed at the National Center for Atmospheric Research (NCAR) in the USA. The study used the Kian-Fritsch (KF), Betts-Miller-Janjic (BMJ) and Grell-Devenyi ensemble (GD) cumulus parameterization schemes across three nested domain configurations. The precipitation simulation results were compared with rainfall observation data from the Tropical Rainfall Measuring Mission. The NCEP analyses, with a 1 1 degree resolution and 26 levels, were utilized to verify the simulation's resulting large-scale circulation pattern, moisture content and relative humidity fields. The 24-hour simulated cumulative rainfall data was created from the different measurements taken at 0300 UTC on July 27, 2005 over Mumbai. It can be observed that the maximum rainfall simulated from the KF, BMJ and GD schemes at 0000 UTC on July 25, 2005, under the initial conditions, was 48, 64 and 32 cm respectively, while the TRMM shows a maximum rainfall of 32 cm at that time. The centre of maximum rainfall was reduced drastically for all 0000 UTC measurements taken on July 26 (the following day), where the initial condition experiments simulated a rainfall amount of only 16 cm. The specific location of the intense rainfall around Mumbai was very-well simulated in the BMJ for 0000 UTC July 25 initial conditions.